The Influence of Company Reputation And Employer Branding On Interest In Applying For Jobs - Putri Siptya Lara (The Scientia Law and Economics Review, 2023)
This study aims to determine the influence of company reputation and employer branding on the interest in applying for jobs as alumni of Hasanuddin University Makassar. This research is quantitative research with a survey method. The Population of this study is alumni of Hasanuddin University who are looking for work using the purposive sampling method. The research sample was 80 respondents. The data collection technique is a questionnaire using a Likert scale. Data analysis techniques using computerized SPSS programs. The results of this study show the influence of company reputation and employer branding on the interest in applying for jobs as alumni of Hasanuddin University Makassar.